Parameteric study of aligned carbon nanotube growth using alcohol catalytic chemical vapor deposition technique - Bistamam, Mohd Shahril Amin (2015)
Carbon nanotubes (CNTs) are nanoscale materials with diameters of few nanometer and length up to several tens of microns. They have been widely used in various industrial applications such as energy storage devices, solar cell application and reinforcement for polymer composites. CNTs are commonly grown using catalytic chemical vapor deposition (CVD) technique. However, until now only few attempts have been made to study CNTs growth with detailed parameters on the growth of CNT alignment using alcohol as carbon feedstock. Thus, the main objective of this research is to further the study on the growth of aligned CNTs (A-CNTs) employing the said technique. A practical and high performance alcohol catalytic CVD (AC-CVD) system has been modified aimed at increasing the quality of gas flow which allows a greater amount of A-CNTs to be produced. The higher quality of gas flow could be produced through a unique shower ring gas supply located above the sample holder that could enhance the growth rate of A-CNTs. The radio frequency magnetron sputtering deposition technique was performed to prepare a substrate-supported catalyst. This consisting of silicon wafer substrate with 300 nm thick silicon oxide layer sputtered with aluminum as catalyst support and cobalt as catalyst with thickness of around 25 nm and below 10nm, respectively, were used to grow A-CNTs. Ethanol (C2H5OH) and argon (Ar) gas were used as CNT precursor and carrier gas, respectively. The AC-CVD processing temperature and time were varied at 700, 725, 750, 775, 800 °C and 3, 5, 7, 10, 15, 30 minutes, respectively, while other parameters were fixed. These parameters were chosen because 700 to 800 °C is the temperature range for CNT growth. Meanwhile, narrow initial time for AC-CVD processing time is due to the highly reactive growth of CNT at time under 10 minutes. The AC-CVD technique successfully produced CNTs with good alignment, high yield, and large area growth with improved controlling of the CNTs characteristics and morphologies. The CNT characterizations study were carried out using field emission scanning electron microscopy (FE-SEM), transmission electron microscopy (TEM), as well as Raman spectroscopy. The best AC-CVD processing temperature and time were found to be at 725 °C and 10 minutes. The as-grown CNTs over various AC-CVD processing temperature and time showed high degree of graphitization, purity and density. The CNTs grown over cobalt catalyst on the silicon wafer substrate are according to the tip-growth mechanism.